1999
DOI: 10.1007/s004670050652
|View full text |Cite
|
Sign up to set email alerts
|

Henoch-Schönlein purpura and pulmonary hemorrhage: a report and literature review

Abstract: Pulmonary hemorrhage, a rare complication of Henoch-Schönlein purpura (HSP) reported primarily in adults and adolescents, is associated with significant mortality. Although it has been suggested that pulmonary hemorrhage also occurs in children with HSP, the few cases reported lack a clear differentiation from pauci-immune vasculitis. We report a prepubertal child with HSP, pulmonary hemorrhage, and immunofluorescence-documented IgA deposits on renal biopsy. Aggressive supportive management and steroid therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…It is more common in children, with a reported incidence of 15 per 100,000. Pulmonary involvement in children is rare [2]. The reported pulmonary complications are impairment in diffusion capacity of the lungs and pulmonary haemorrhage [3].…”
Section: Discussionmentioning
confidence: 99%
“…It is more common in children, with a reported incidence of 15 per 100,000. Pulmonary involvement in children is rare [2]. The reported pulmonary complications are impairment in diffusion capacity of the lungs and pulmonary haemorrhage [3].…”
Section: Discussionmentioning
confidence: 99%
“…In our unit more than 550 cases of HSP have been followed; 42% had renal involvement, but we had not encountered pulmonary haemorrhage with HSP in our series. Chaussain et al [19] showed impairment of lung diffusion capacity to be a common finding in children with HSP, but pulmonary haemorrhage in Henoch-Schönlein purpura is extremely rare: a total of 20 cases with an age range between 4.5 and 78 years have been reported [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Eleven cases were seen in childhood (4.5-17 years).…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common vasculitis seen in children. Although renal involvement is frequent (60%), pulmonary involvement is rare and it significantly increases the mortality [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. There are few reports regarding pulmonary haemorrhage in HSP.…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse pulmonary hemorrhage has been increasingly recognized as a complication of the above-mentioned diseases (3). Pulmonary hemorrhage may occur in patients with HenochSchonlein purpura (4,5), but is quite uncommonin patients with Wegener's granulomatosis whodo not have granulomatous lesions in the lung. Therefore, her clinical presentations such as melena, colonic purpura and skin purpura with histology of leukocytoclastic vasculitis in combination with pulmonary hemorrhage should be interpreted as Henoch-Schonlein purpura.…”
Section: Case Reportmentioning
confidence: 99%